EFEKTIFITAS DAN KONTRIBUSI PENERIMAAN PAJAK HOTEL DAN PAJAK RESTORAN TERHADAP PENDAPATAN ASLI DAERAH (PAD) KOTA PEKANBARU - Khoirul Abiddin; Yusbar Yusuf; Wahyu Hamidi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
Revenue is a local tax revenues from charges, levies, separated management of regional assets and other income. Hotel and restaurant taxes are included in the tax area. Hotel and restaurant is a potential sector in improving the effectiveness of the hotel and restaurant tax revenues and contributions provided by hotels and restaurants can spur economic development of Pekanbaru. The purpose of this study to determine the revenue growth, the effectiveness of tax collection and the contribution of the hotel and restaurant tax to the increase in revenue in the year 2010-2014 based Pekanbaru and the realization of the target. The analytical method used is descriptive method to analyze the data of actual hotel and restaurant tax years 2010-2014.The results showed that the growth of tax revenue in the hotel and restaurant tax Pekanbaru from 2010 to 2014 experienced growth fluctuates from year to year. The level of effectiveness of tax revenue in the hotel and restaurant tax Pekanbaru from 2010to 2014 has fluctuated from year to year but is still in a effective criterion. Tax contribution rate hotel and restaurant tax to PAD Pekanbaru from 2010 to 2014 experienced growth fluctuates each year included in the very contributive criteria. Overall the number PAD is not only influenced by the hotel tax and restaurant tax, but there are still other types of receipts that may affect the amount of overall revenue.Keywords: Effectiveness, Contributions, Hotel Tax, Restaurant Tax, Local Revenue